2004
DOI: 10.1562/0031-8655(2004)79<55:dsosha>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Self-aggregation of Synthetic 3-(1-Hydroxyethyl)-bacteriopyrochlophyll-a as a Novel Photosynthetic Antenna Model Absorbing Near the Infrared Region¶

Abstract: 3-Deacetyl-3-(1-hydroxyethyl)bacteriopyrochlorophyll-a (1), 7,8-dihydrobacteriochlorophyll-d possessing 8-ethyl, 12-methyl and 17(4)-phytyl groups, was prepared by modifying naturally occurring bacteriochlorophyll-a. The synthetic 3(1)-epimers were separated by high-performance liquid chromotagraphy, and the absolute configuration at the 3(1)-position was determined by derivatization of 1 to a structurally determined chlorin. A dichloromethane solution of 3(1)R-1 or 3(1)S-1 was diluted with a 1000-fold volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Additionally, naturally occurring BChls take both R and S configurations as the 3 1 -stereochemistry. In vitro aggregates of BChls and their zinc analogues showed that their supramolecular structures were dependent on the homologues and epimers (Balaban et al , 1997Chiefari et al 1995;Ishii et al 2000;Kunieda et al 2004;Miyatake et al 2001;Mizoguchi et al 2000Mizoguchi et al , 2002Saga et al 2001;Steensgaard et al 2000;Tamiaki et al 1998Tamiaki et al , 2000Tamiaki et al , 2004. A similar observation was obtained by molecular modeling studies on self-aggregates of zinc analogues (Yagai et al 2001).…”
Section: Introductionsupporting
confidence: 67%
“…Additionally, naturally occurring BChls take both R and S configurations as the 3 1 -stereochemistry. In vitro aggregates of BChls and their zinc analogues showed that their supramolecular structures were dependent on the homologues and epimers (Balaban et al , 1997Chiefari et al 1995;Ishii et al 2000;Kunieda et al 2004;Miyatake et al 2001;Mizoguchi et al 2000Mizoguchi et al , 2002Saga et al 2001;Steensgaard et al 2000;Tamiaki et al 1998Tamiaki et al , 2000Tamiaki et al , 2004. A similar observation was obtained by molecular modeling studies on self-aggregates of zinc analogues (Yagai et al 2001).…”
Section: Introductionsupporting
confidence: 67%
“…Substrate Chlide a was prepared according to previously reported methods (Tsukatani et al, 2013b). and the substrate 3V-BChlide d was synthesized from Chlide a as described previously (Kunieda et al, 2004). Activities of BchF and BchV enzymes were assayed in a mixture containing 20 μM substrate and supernatant proteins at 2.5 mg ml −1 in a buffer containing 25 mM Tris-HCl (pH 7.8), 7.5 mM NaCl, and 10% dimethylsulfoxide after incubation at 35°C for 60 min in the dark.…”
Section: Activities Of Bchf and Bchv Enzymes In Vitromentioning
confidence: 99%
“…1) in nonpolar organic solvents as chlorosomal models (1 2-16), indicating that linear location of hydroxy, keto-carbonyl groups and a central coordinative metal including Mg, Zn and Cd in a molecule is necessary for such a self-aggregation. Natural self-aggregative BChl-c/d/e have chlorin (= 17,18-dihydroporphyrin) n-systems, and we have found that a bacteriochlorin (= 7,8,17,18-tetrahydroporphyrin) moiety was also useful for its self-aggregation (17). In this study, we report on the synthesis of zinc 3'-hydroxy-13'-0x0-porphyrins Zn-112 ( Fig.…”
Section: Introductionmentioning
confidence: 95%